Análise in sílico de genes de resistência aos nematoides das galhas em espécies do gênero Lactuca - Moreira, Michelle de Lima (2022)
Lettuce (Lactuca sativa L) is a vegetable of Mediterranean origin belonging to the Asteraceae family, order Asterales. In addition to being one of the most important vegetables grown in the world, it is also the most consumed leafy vegetable in Brazil. One of the difficulties in producing it is related to infestation by phytopathogens in production areas. Among these, Meloidogyne, a root-knot nematodes, stand out, especially M. incognita and M. javanica. These nematodes are common in higher temperatures conditions occurring in all Brazil regions, causing great crops damage. The main disease symptom is the formation of roots galls, damaging the vascular tissues, which, in addition to the damage caused by the pathogen itself, also increases the plant susceptibility to fungi and bacteria that cause another disease. The use of resistant lettuce cultivars is an efficient and safe method for nematodes control, because in addition to restricting the nematode reproduction and reducing the production cost, it does not impact the environment. There are still few works on nematode resistance genes in lettuce and, still, commercial cultivars that show resistance are not available. Thus, the objective of this work is to search for nematode resistance genes in lettuce, using genomic analysis techniques by bioinformatics. A search for NBS-LRR genes for resistance to Meloidogyne spp was carried out, as it was identified that these genes are responsible for resistance to Meloidogyne spp in several species. Subsequently, the sequences found were characterized by Blastx and InterproScan and a phylogenetic analysis was performed using the neighbor joining method. Bioinformatics resources were essential for the characterization of resistance genes, so that at the end of this work it was possible to identify 2 genes of the NBS-LRR class with the potential to confer resistance to Meloidogyne spp in Lactuca saligna. This result opens perspectives for further work aimed at improving the resistance to Meloidogyne spp in lettuce, since L. saligna is a species already used in lettuce breeding programs. Keywords: Lactuca sativa, Meloidogyne spp, resistance genes, NBS-LRR